Collaborative Governance in Tourism Development Through Heart Venture Film in Wonosobo District - Fadhlan, Muhammad; Subarsono, Agustinus (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This research aims to understand the implementation of the collaborative governance process in tourism development through the film Heart Venture in Wonosobo Regency based on the 5 stages of the collaboration process developed by Ansell and Gash: face-to-face dialogue, trust building, commitment to process, shared understanding, and intermediate outcomes. The method used is qualitative, with data collection techniques including initial observation, determining informants, interviews, document study and testing the validity of the data. This research also examines the obstacles and challenges in implementing collaborative governance by referring to the dynamic aspects of collaboration developed by Emerson consisting of principled involvement, shared motivation, and joint action. The research results show that the five stages in the collaboration process have been implemented in tourism development through the film Heart Venture. The obstacles and challenges of collaboration are; 1) human resources, 2) budget constraints, 3) time, 4) weather, and 5) pre history.